Supplementation of natural minerals on the performance of broiler (Bangladesh Journal of Animal Science, 2020)
An experiment was conducted to evaluate the efficacy of AZOMITE® as source of natural minerals on growth performance of commercial broiler. A total of 1,020 day-old Cobb 500 male broiler chicks were randomly allocated to 5 dietary treatments with 6 replications per treatment having 34 chicks in each pen. The five dietary treatments were: (i) basal diet without AZOMITE®, (ii) basal diet with 0.25% AZOMITE®, (iii) basal diet with 0.50% AZOMITE® which was recommended by manufacturer, (iv) basal diet with 0.75% AZOMITE® and (v) basal diet with 1.0% AZOMITE®. Broilers were reared in open-sided gable type house for a period of 32 days. Results showed that the supplementation of AZOMITE® had significant effect on growth performance (p